1988
DOI: 10.1038/sc.1988.48
|View full text |Cite
|
Sign up to set email alerts
|

Self-neglect of spinal injured patients

Abstract: SummarySelf-neglect is a recognised, but poorly emphasised, complication of spinal cord injury, with a prevalence in this study of 9°'0 of a consecutive sample of 400 patients. Self-neglect may be the presenting symptom of problems related to adjustment to disability, a major depressive disorder (DSM III criteria), or a clear and rational wish to die (existential self-neglect). Management is discussed, emphasising the importance of respecting spinal injured patients' autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…A few of these, as well as deaths from other causes may in fact have been suicides by self-neglect (Macleod, 1988). However, any such deaths were not included in this study because we had no way to confirm suicidal intentions.…”
Section: Discussionmentioning
confidence: 99%
“…A few of these, as well as deaths from other causes may in fact have been suicides by self-neglect (Macleod, 1988). However, any such deaths were not included in this study because we had no way to confirm suicidal intentions.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition to the emotional distress experienced, problems with adjustment can affect other areas of functioning. For example, it has been suggested that problems with adjustment are linked to self-neglect, 4 which can in turn impact on the physical well-being and increase the likelihood of the onset of secondary complications. 5 Difficulties have also been linked to substance abuse, 6 which may contribute to further health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of self-neglect (such as non-compliant behavior or passive behavior resulting in physical problems) has also been found to be high when depressive illness is involved. 6 Australian data on divorce trends following SCI is lacking, however, increased divorce trends in the USA demonstrate the di culties involved in adjusting to SCI. 7 Drug abuse is also a potentially increasing problem in this population.…”
Section: Introductionmentioning
confidence: 99%